HYBRID NON-GOVERNMENTAL ORGANIZATIONS (NGOS): STUDY OF THE MANGROVE FOREST REHABILITATION PROGRAM IN INDONESIA BY THE BLUE FOREST - Aswin Baharuddin (FISIP UNHAS, 2019)
This study aims to analyze the strategies and implications of implementing a mangrove forest rehabilitationprogram carried out by a Non-Government Organization, namely Blue Forest. To analyze the problems in thisstudy Green Perspectives and Hybrid NGOs are used. This research was conducted in 2017 and took locations inMakassar and Takalar. This study uses a qualitative approach and data collected through interviews, literaturestudies and document review. This research found that in realizing its objectives, Blue Forest combines policyadvocacy and direct action to rehabilitate mangrove forests with the community